2023
DOI: 10.3390/nu15020416
|View full text |Cite
|
Sign up to set email alerts
|

Interlinkages between Climate Change and Food Systems: The Impact on Child Malnutrition—Narrative Review

Abstract: The pandemics of obesity, undernutrition, and climate change represent severe threats to child health. They co-occur; interact with each other to produce sequelae at biological, psychological, or social levels; and share common underlying drivers. In this paper, we review the key issues concerning child diet and nutritional status, focusing on the interactions with climate and food systems. Inadequate infant and young child feeding practices, food insecurity, poverty, and limited access to health services are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 91 publications
2
17
0
Order By: Relevance
“…Blended diets are often used in combination with commercial enteral formulae which is a good way of nutritional and energy enrichment of blended diets. However, it is reported that families require a good education, engagement and support from dietitians to properly use blended diets for enteral feeding 5. Current data and evidence given by this review confirm the findings of previous reports.…”
Section: Commentarysupporting
confidence: 81%
See 1 more Smart Citation
“…Blended diets are often used in combination with commercial enteral formulae which is a good way of nutritional and energy enrichment of blended diets. However, it is reported that families require a good education, engagement and support from dietitians to properly use blended diets for enteral feeding 5. Current data and evidence given by this review confirm the findings of previous reports.…”
Section: Commentarysupporting
confidence: 81%
“…In addition, the use of blended diets is also linked to sustainable nutrition. However, the environmental ramifications of blended diets versus artificial nutrition have not been thoroughly studied, warranting further investigation 5…”
Section: Contextmentioning
confidence: 99%
“…Malnutrition is a major problem in the Horn of Africa, with South Omo being one of the most affected areas ( 31 , 32 ). While we are writing about the “perfect storm” of the COVID-19 pandemic, climate change and the wheat crisis are worsening the risk for this already extremely frail population ( 31 , 33 ). A study conducted in South-West Ethiopia before and during the COVID-19 pandemic found a recovery rate from severe acute malnutrition (SAM) of 68% in children aged 6–59 months, which was lower than the minimum accepted international standard of 75%, and a lower recovery rate when SAM was comorbid with pneumonia ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The epidemics of obesity, undernutrition, and climate change interact to produce shared threats to child health. Even within the United States, the world’s wealthiest economy, around 11% of children are food insecure (Agostoni et al, 2023; Ullmann et al, 2022). Preventative measures taken in the short term to address these issues are important for mitigation, future adaptation, and resilience.…”
Section: Solutions Include Mitigation Adaptation Resiliencementioning
confidence: 99%